Hydrochemical characteristics of groundwater for domestic and irrigation purposes in madhuranthakam, tamil nadu, india (2011)
Hydrochemical study was carried out in Madhuranthakam located near Chennai in Tamil Nadu, India with an objective of understanding the suitability of local groundwater quality for domestic and irrigation purposes. Twenty groundwater samples were collected in February 2002 and analysed for physical and chemical parameters. groundwater in this area was found to be within the desirable Bureau of Indian Standards and World Health Organisation limits for drinking water. Ca-HCO  was the dominant groundwater type. groundwater in this area was assessed for irrigation purposes on the basis of sodium percentage (Na%), magnesium hazard (MH), residual sodium carbonate (RSC), sodium absorption ratio (SAR), permeability index (PI) and United States department of Agriculture (USdA) classification. Most of the groundwater samples were suitable for irrigation, except in a few locations (15%) based on MH. Overall the groundwater quality was suitable for drinking and domestic purposes and permissible for irrigation activities.